10 Common Palms of the Tampa Bay Area - Gitta Hasing; Andrew K. Koeser; Melissa H. Friedman; Timothy K. Broschat (EDIS)
Palms often serve as key specimens in urban landscape designs. Despite this, their identity is often unknown to Florida’s new, seasonal, and even long-term residents. This 10-page fact sheet serves as a quick reference for some of the most common palms found in North and Central Florida and the Tampa Bay Area in particular. Written by Gitta Hasing, Andrew K. Koeser, Melissa H. Friedman, and Timothy K. Broschat, and published by the Environmental Horticulture Department, June 2016.